Variable data-window-size recursive least-squares algorithm for dynamic system identification - Cho, Hyeonwoo; Yu, Son-Cheol (Electronics letters, 2015)
A variable data-window size for the recursive least-squares algorithm is proposed. Using the window-size selection criterion, the window size can be suitably adjusted for the conditions of the system parameters to be estimated.